Якість продукції як об’єкт управління - Осадчук, Оксана Павлівна (My University, 2011)
В статті досліджено поняття якості продукції як об’єкта управління в межах виробничої діяльності підприємства. Визначено сутність категорії управління якістю та запропоновано авторське визначення поняття ефективне управління якістю. The article is investigated the concept of the good’s quality as the control object within the limits of production activity of the interprise. It is determined the main point of the quality control and given the author’s definition of effective quality management. Quality management, of its essence, is a complex economic category, that’s why for better understanding are given all the types and principles of its development.
Keywords: якість продукції; підприємство; якість; quality of products; enterprise; quality; кафедра економіки праці та менеджменту